2011
DOI: 10.2533/chimia.2011.356
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Photosynthesis at Soft Interfaces

Abstract: Theconceptofartificialphotosynthesisatapolarisedliquidmembraneispresented.Itincludestwo photosystems,oneateachinterfaceforthehydrogenandoxygenevolutionrespectively.Bothreactionsinvolve protoncoupledelectrontransferreactions,andsomeultrafaststepsatthephotosensitizationstage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…17,91,246 Insights from such studies may potentially find applications in future artificial photosynthesis systems. 247,248 The underlying fundamental reasons for any enhanced photocurrents are as yet unresolved, with electrocatalytic and/or plasmonic factors needing to be considered. Nagatani et al 246 and Schaming et al 91 observed increased photocurrents that may be attributed to increased absorption due to surface plasmons and light-trapping effects, improved charge separation due to a localized intense electromagnetic field, or perhaps electron-storage effects that alter the Fermi level of the interfacial gold nanofilm.…”
Section: Plasmonic Photocatalysismentioning
confidence: 99%
“…17,91,246 Insights from such studies may potentially find applications in future artificial photosynthesis systems. 247,248 The underlying fundamental reasons for any enhanced photocurrents are as yet unresolved, with electrocatalytic and/or plasmonic factors needing to be considered. Nagatani et al 246 and Schaming et al 91 observed increased photocurrents that may be attributed to increased absorption due to surface plasmons and light-trapping effects, improved charge separation due to a localized intense electromagnetic field, or perhaps electron-storage effects that alter the Fermi level of the interfacial gold nanofilm.…”
Section: Plasmonic Photocatalysismentioning
confidence: 99%
“…S5 showed the intensity of the signal at 5.60 ppm for the watersandwich dimer declining and new signals appearing with time. Analysis of these data shows that the photolysis of the watersandwich dimer followed [8] and [9] rather than [10][11][12] as demonstrated below by computations to form a hydroxo complex, i.e., ½Cp 2 Os IV ðOH − Þ þ (δ ¼ 6.14 ppm) and a hydride complex. The hydroxo species reacts further to a peroxo complex, i.e., Cp 2 Os IV -ðO 2 Þ (δ ¼ 6.02 and 5.56 ppm).…”
Section: H Nmr Analysismentioning
confidence: 97%
“…More generally, we have shown that voltammetry at the interface between two immiscible electrolyte solutions (ITIES) is a very useful tool to study proton coupled electron transfer reactions involving aqueous protons and organic electron donors (8)(9)(10). This methodology has been also applied to molecular electrocatalysis where an amphiphilic catalyst is used to complex oxygen to facilitate its reduction as recently reviewed (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Liquid-liquid interfaces, or interfaces between two immiscible electrolyte solutions (ITIES), possess features suitable to engineer innovative artificial photosynthetic Z-schemes capable of driving energetically uphill chemical reactions. 4 Waterorganic interfaces can be ''dye-sensitised'' with molecular photosensitisers, 5 or trap semiconductor nanomaterials through interfacial surface tension. 6 A hydrophobicity gradient across the ITIES facilitates spatial separation of charge carriers on either side of the interface.…”
Section: Introductionmentioning
confidence: 99%